Informatics on Drug Repurposing for Breast Cancer - Zhou H; Liu H; Yu Y; Yuan X; Xiao L (Dove Medical Press, 2023)
Hui Zhou,1,2,* Hongdou Liu,3,* Yan Yu,3 Xiao Yuan,3,4 Ling Xiao5 1Department of Lymphoma and Hematology, The Affiliated Cancer Hospital of Xiangya School of Medicine, Central South University, Changsha, Hunan, People's Republic of China; 2Department of Lymphoma and Hematology, Hunan Cancer Hospital, Changsha, Hunan, People's Republic of China; 3Department of Laboratory Diagnosis, Changsha Kingmed Center for Clinical Laboratory, Changsha, Hunan, People's Republic of China; 4Department of Laboratory Diagnosis, Guangzhou Kingmed Center for Clinical Laboratory, Guangzhou, Guangdong, People's Republic of China; 5Department of Histology and Embryology of Xiangya School of Medicine, Central South University, Changsha, Hunan, People's Republic of China*These authors contributed equally to this workCorrespondence: Ling Xiao, Department of Histology and Embryology of Xiangya School of Medicine, Central South University, Changsha, Hunan, People's Republic of China, Tel +86-13974871376, Email xiaolingcsu@csu.edu.cn Xiao Yuan, Changsha Kingmed Center for Clinical Laboratory, Changsha, Hunan, People's Republic of China, Tel +86-18662520739, Email hn-yuanxiao@kingmed.com.cnAbstract: Moving a new drug from bench to bedside is a long and arduous process. The tactic of drug repurposing, which solves "new" diseases with "old" existing drugs, is more efficient and economical than conventional ab-initio way for drug development. Information technology has dramatically changed the paradigm of biomedical research in the new century, and drug repurposing studies have been significantly accelerated by implementing informatics techniques related to genomics, systems biology and biophysics during the past few years. A series of remarkable achievements in this field comes with the practical applications of in silico approaches including transcriptomic signature matching, gene-connection-based scanning, and simulated structure docking in repositioning drug therapies against breast cancer. In this review, we systematically curated these impressive accomplishments with summarization of the main findings on potentially repurposable drugs, and provide our insights into the current issues as well as future directions of the field. With the prospective improvement in reliability, the computer-assisted repurposing strategy will play a more critical role in drug research and development.Keywords: drug repurposing, breast cancer, CMap, network, molecular docking